TOWARDS MORE SUSTAINABLE WASTE MANAGEMENT - PROPOSAL FOR THE IMPLEMENTATION OF A DEPOSIT AND REFUND SYSTEM IN NIGERIA - Oluwaleye, Michael (My University, 2017)
The increase in population level, economic development, and changes in standard of living in Nigeria results in an exponential increase in a waste generation most especially beverage container packages. Consequently, more unregulated landfills are open on a daily basis, causing health and environmental hazards. The situation has raised many concerns whereby government at all levels are channeling significant resources to ameliorate the menace, but the effort is yet to yield any significant result. Though, improper waste disposal is not a new situation in Nigeria. Many studies have been conducted in the past and several recommendations have been adopted like privatization of waste management services, provision of more waste collection bins, the opening of regulated landfills, monthly environmental sanitation, integrated media selection strategy, etc. However, mountains of waste are becoming an eyesore in the country. Therefore, by adopting an economic-incentive mechanism known as deposit and refund system (DRS), this study proffer solution to the existing waste management problem by conceptualizing deposit and refund system blueprint in the Nigerian context. The blueprint encompasses all deposit system framework, influencing factors and as well all actors that are involved in DRS. In that regard, DRS in Nigeria becomes the case study of this research. Both qualitative and quantitative research methods are utilized to collect data for this research. Face to face interview was conducted with PALPA, the company that manages return system of beverage packages in Finland. Questionnaires were administered to Nigerians in order to examine the factors that have hindered the efficiency of waste container recycling in Nigeria. Subsequently, data analysis was carried out in a qualitative and quantitative approach, respectively. The results show that DRS is possible to be implemented in Nigeria provided that all beverage stakeholders, including the government have one major goal, i.e., to salvage the environment. Moreover, this study identified that due to the present economic, environmental and political situations in Nigeria, DRS approach should be a mandatory-mechanism instrument. In addition, the DRS should be operated as a private entity, to avoid inefficient and ineffective waste container recycling service.
Keywords: Waste management system; Deposit and refund system; Beverage container; stakeholders.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|